Hydrological Analysis for Spatial Plan of Hamparan Rawang District to support Resilient Urban Development - Gustiabudi, Rahmat (Department of Physics, Universitas Negeri Padang, 2025)
Hamparan Rawang District plays a crucial role in the overall spatial planning and development strategy of Sungai Penuh City. However, Hamparan Rawang District encounters significant environmental challenges that threaten its natural resources and ecosystems, biodiversity, and overall sustainable development and resilience. Hydrological analysis and spatial planning of Hamparan Rawang District is conducted for disaster mitigation and resilient urban development strategies. The descriptive analysis method is carried out by direct observation of the characteristics and potential problems in Hamparan Rawang District. During the rainy season, several places in the watershed in the Hamparan Rawang District are prone to flooding. In 2016, the area of ​​flood inundation in Hamparan Rawang District reached 11 percent of the area of ​​Hamparan Rawang District. The area of ​​flood inundation increased in 2020 to 18.58 percent of the area. In general, drainage channels in Hamparan Rawang District have reached almost the entire city area.. However, its maintenance management has not been optimal, this is evidenced by the overflow of water onto the road surface when it rains.